2016
DOI: 10.1186/s40064-016-1913-2
|View full text |Cite
|
Sign up to set email alerts
|

The economic status of older people’s households in urban and rural settings in Peru, Mexico and China: a 10/66 INDEP study cross-sectional survey

Abstract: Few data are available from middle income countries regarding economic circumstances of households in which older people live. Many such settings have experienced rapid demographic, social and economic change, alongside increasing pension coverage. Population-based household surveys in rural and urban catchment areas in Peru, Mexico and China. Participating households were selected from all households with older residents. Descriptive analyses were weighted back for sampling fractions and non-response. Househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…We observed in our study that the higher the age group of the heads of household, the lower the proportion of moderate/severe FI, which could be down to contributions by older people to family income [34]. Data from the National Family Expenditure Study indicated that FI was less prevalent in households that included older people [15].…”
Section: Discussionmentioning
confidence: 82%
“…We observed in our study that the higher the age group of the heads of household, the lower the proportion of moderate/severe FI, which could be down to contributions by older people to family income [34]. Data from the National Family Expenditure Study indicated that FI was less prevalent in households that included older people [15].…”
Section: Discussionmentioning
confidence: 82%
“…72 The classification and assignment of occupation are differently defined across studies and settings and weakly captured, especially for the retired population. 69 Late-life income may be affected by the association of pensions with formal employment, 73 thereby influencing PHC utilization.…”
Section: Discussionmentioning
confidence: 99%
“…The 10/66 rural catchments: communities in Canete coastal province, Peru; Daxing, 40kms from Beijing in China; villages in Morelos, a mountainous district 70kms from Mexico City; rural communities in Dunukofia, Anambra State, Nigeria are characterised by higher proportions of people working in the informal economy, carrying out activities such as farming, fishing or trade. For detailed description of the pensions and health insurance context in each setting, and the compositional characteristics of the households and older individuals, see our open access protocol paper [ 13 ] and paper describing the economic status of INDEP study households [ 8 ]).…”
Section: Design and Methodsmentioning
confidence: 99%
“…Nonetheless, implementation has been slow. There is evidence to suggest that without further transformations of labour markets, social pensions alone may do little to address unequal distributions of pension entitlements and therefore have a minimal overall impact upon poverty [ 8 ]. Likewise, despite the roll-out of government health insurance packages, no LMIC has achieved universal coverage [ 9 ].…”
Section: Introductionmentioning
confidence: 99%